Adsorption Capacity of Activated Carbon of Peanut Shells on Fe Removal - Agil Harnowo Putra; Miftahul Jannah; Euis Nurul Hidayah; Okik Hendriyanto Cahyonugroho (Nusantara Science and Technology Proceedings)
Cellulose contained in peanut shells which are agricultural waste is considered to be potential as an adsorbent for removing heavy metals. Therefore, it is necessary to analyze the capacity of absorbance or the ability of meshes in the continuous adsorption process in removing heavy metal Fe in well water. The feasibility of an agricultural waste related to its use as an adsorbent has also been studied in this study through characterization by FTIR test which aims to determine the presence of cellulose organic compounds that play a role in the process of heavy metal adsorption. While the study of adsorption capacity in this study uses a continuous process that is generally carried out by Thomas modeling. Where in this study a continuous adsorption process was carried out to obtain saturation time from the adsorption of peanut shells in absorbing Fe metal. So that the absorbance capacity obtained from the once used activated carbon peanut shell has been made. In this study, a continuous adsorption process was carried out with a mass variation of 250 gr and 500 gr. This continuous adsorption process is obtained. The highest price of Constant Thomas (Kth) and the price of absorbance capacity (qo) is using activated carbon peanut shells with the use of 500 grams following the Thomas equation model y = -0.1701x + 3.3142 with a correlation coefficient (R²) = 0.4767 while the breakthrough point was reached in the 60th minute after well water through the bed